Pengembangan Majalah IPS sebagai Media Pembelajaran pada Materi Interaksi Budaya Masa Kerajaan Islam di SMPN 3 Kedungwaru Tulungagung (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Education is one of the key aspects in developing high-quality human resources. Along with the advancement of time, teachers are expected to create effective learning media in the teaching and learning process. Learning media should also be adapted to students’ learning styles, such as visual, auditory, and kinesthetic.The purpose of this study is to develop and test the feasibility, practicality, and effectiveness of an IPS (Social Studies) magazine as a learning medium for Grade VIII students at SMPN 3 Kedungwaru Tulungagung. This research is a development study using the ADDIE R&D model. Data were collected through interviews, needs and learner characteristic analysis, feasibility and practicality questionnaires, as well as pretest and posttest results.The findings of this study show that the IPS magazine is highly feasible, with a feasibility percentage of 89.91% from material experts and 91.18% from media experts. The practicality results based on teacher questionnaires reached 94.87%, and student responses reached 88.62%, indicating that the IPS magazine is highly practical. The effectiveness of the media was proven through the Paired Sample Test, which showed a significance value of 0.000 < 0.05, indicating a difference in results before and after using the IPS magazine. Therefore, the IPS magazine is considered effective for use in the learning process.